Assessment in Forensic Practice / A Handbook - Beech Anthony; Browne Kevin D; Chou Shihning; Craig Leam A (Wiley Blackwell, 2017)
Introduction, Criminal Case Assessments, Case Formulation and Risk Assessment, Assessment of Violence and Homicide, Sexual Offenders, The Assessment of Firesetters, Forensic Psychological Risk Assessment for the Parole Board, Forensic Psychological Risk Assessment for the Parole Board, Behavioral Assessment in Investigative Psychology, Offenders with Mental Disorders, Assessing Risk of Violence of Offenders with Mental Disorders, Assessing Mental Capacity and Fitness to Plead in Offenders with Intellectual Disabilities: Implications for Practice, Offenders with Personality Disorder Diagnoses, Offenders and Substance Abuse, Family Violence, Community Approaches to the Assessment and Prevention of Intimate Partner Violence and Child Maltreatment, Psychological Assessment of Parenting in Family Proceedings, Perpetrators of Intimate Partner Violence, Policy and Practice, Assessment of Hostage Situations and Their Perpetrators: In the Context of Domestic Violence, Assessing the Sexually Abused Child as a Witness, Working with Young Offenders, The Ethics of Risk Assessment, Index.